Gender Discrimination and Its Effects on Women’s Health: In the Reference to Barahataal Rural Municipality Ward no. 2, Surkhet - Paudel, Bal Krishna; Bharati, Ranjeeta (Journal of Gurubaba, 2024)
This study entitled Gender Discrimination and its Effects on Women’s Health: In the reference to Barahataal Rural Municipality ward no.2, Surkhet was carried out to analyze the effects of Gender Discrimination and its effects on women’s health in Barahataal Rural Municipality ward no-2, Surkhet. In this study exploratory type of research design is carried out by the researcher. In this study respondents were selected by using simple random sampling method. The structure interview schedule was used as the tool for data collection. The interview schedule was divided into three parts. The first part of the interview schedule was related to the knowledge of the gender discrimination, the second part related to the situation of gender discrimination and third part of interview schedule were related to the effects of gender discrimination of the study area.In the study area, the facing health hazards by the respondents (50 percent), Majority20 percent of respondents were faced low esteem due to the gender discrimination. Most of the 56.8 percent of respondents were felt maintain strict law and order to solve the problems of gender discrimination. Similarly 50 percent of respondents felt raising awareness to solve the problems of gender discrimination in Barahataal Rural Municipality ward no. 2, Surkhet.